The impact of gum additives on the process of dough forming and quality of macaroni products - Yurchak, Vera; Palyvoda, Svetlana; Holikova, Tatiana (My University, 2008)
This paper deals with the impact of natural gums introduction upon the dough kneading, forming, and, as a result, upon the quality of macaroni products. The best bettering effect has been observed at the addition of guar gum and locust bean gum. The best characteristics of macaroni products were observed at the dosage of gums of 0,15 % to the mass of flour and included the following: the bettering of surface quality, strength and cooking properties of macaroni products.
Keywords: macaroni products; wheat flour; kneading; pressing; макаронні вироби; хлібопекарське борошно; замішування; формування; макаронные изделия; хлебопекарная мука; замешивание; формование; кафедра технології хлібопекарських і кондитерських виробів; кафедра готельно-ресторанної справи